2017
DOI: 10.1002/pi.5493
|View full text |Cite
|
Sign up to set email alerts
|

Probing the compatibility and interaction of energetic binders based on 3,3‐bis(azidomethyl)oxetane with some explosives: thermal, interfacial and simulation studies

Abstract: Several polymer binders based on 3,3-bis(azidomethyl)oxetane (BAMO) were studied to explore the compatibility and interaction of the energetic binders with three common energetic oxidants. The compatibilities were studied by differential scanning calorimetry and ratings were obtained according to evaluated standards. The results showed that all the binders based on BAMO had good compatibility with cyclotrimethylenetrinitramine, cyclotetramethylenetetranitroamine and hexanitrohexazaiso-wurtzitane. The work of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, the interfacial tension ( γ s1,s2 ) and work of adhesion ( W a ) between HTPE/N100 binder containing different contents of MHBPE and RDX were investigated according to the method of Li et al . 17 and the results are shown in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the interfacial tension ( γ s1,s2 ) and work of adhesion ( W a ) between HTPE/N100 binder containing different contents of MHBPE and RDX were investigated according to the method of Li et al . 17 and the results are shown in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angles and the polar and dispersion components (γ p , γ d ) of the surface free energy (γ) of the binders as functions of the content of MHBPE are listed in Tables 4 and 5, respectively. Therefore, the interfacial tension (γ s1,s2 ) and work of adhesion (W a ) between HTPE/N100 binder containing different contents of MHBPE and RDX were investigated according to the method of Li et al 17 and the results are shown in Table 6. As depicted in Fig.…”
Section: Principal Mechanisms Related To the Mechanical Performancementioning
confidence: 99%
“…Poly-BAMO itself has attracted interest due to its higher azide content than GAP. BAMO was found to be compatible with other energetic materials such as CL-20, HMX, and RDX [19][20]. Unfortunately, GAP and BAMO have rather poor mechanical properties, GAP's properties are better.…”
Section: Azido Polymersmentioning
confidence: 88%